2002
DOI: 10.1021/jp020206h
|View full text |Cite
|
Sign up to set email alerts
|

BAC-MP4 Predictions of Thermochemistry for Gas-Phase Compounds in the Si−H−O−Cl System

Abstract: A self-consistent set of thermochemical parameters for 39 molecules in the Si−H−O−Cl system have been calculated using the BAC-MP4 method. The BAC-MP4 method combines ab initio electronic structure calculations with empirical corrections to obtain accurate heats of formation. Both stable and radical species are included in the study, as well as several complexes formed by reaction with gas-phase water. Although there are almost no experimental data available for comparison, trends within homologous series and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…The SiCl 2 /O 2 system has been studied previously by ab-initio calculations using the BAC-MP4 method by Allendorf and Melius. 29 They found the initial linear triplet Cl 2 SiOO adduct which could lose an O( 3 P) to make Cl 2 Si=O. They also found that the linear singlet Cl 2 SiOO adduct collapses to the cyclic form (at the HF/6-31G(d) level) which is very much more stable.…”
Section: Mechanistic Interpretation and Ab Initio Calculationsmentioning
confidence: 96%
“…The SiCl 2 /O 2 system has been studied previously by ab-initio calculations using the BAC-MP4 method by Allendorf and Melius. 29 They found the initial linear triplet Cl 2 SiOO adduct which could lose an O( 3 P) to make Cl 2 Si=O. They also found that the linear singlet Cl 2 SiOO adduct collapses to the cyclic form (at the HF/6-31G(d) level) which is very much more stable.…”
Section: Mechanistic Interpretation and Ab Initio Calculationsmentioning
confidence: 96%
“…With limited experimental studies, quantum chemistry calculations have been used to predict the enthalpies of formation of fluorinated and chlorinated silanes and free radicals [17,29,[47][48][49][50][51][52][53][54][55][56][57][58][59] and of cations SiH x F y + , SiF x + , and SiCl x + [29,51,[53][54][55]60,61], while none on brominated species. Theoretical studies have found large discrepancies to as well as occasional agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…= DH1(8a.1) + DH1(8a.2) DH1(8a)/ kJ mol À1 = À519 + 597 = 78 This rather small value may be thought of as combining the O-O bond dissociation enthalpy in a silyl peroxide (H D 1(Cl 3 SiO-OSiCl 3 ) = 235 kJ mol À1 )54 and the strain enthalpy of a typical Si-containing 3-membered ring (157 kJ mol À1 ). (b)DH1 for this reaction used the analogy of the Si-Cl bond enthalpy (501 kJ mol À1 ) in Cl 2 Si(OH) 254 and the p-bond enthalpy obtained by considering the dehydrogenation process of H 2 Si(OH) 2 to give HSi(QO)OH.…”
mentioning
confidence: 99%
“…= DH1(8a.1) + DH1(8a.2) DH1(8a)/ kJ mol À1 = À519 + 597 = 78 This rather small value may be thought of as combining the O-O bond dissociation enthalpy in a silyl peroxide (H D 1(Cl 3 SiO-OSiCl 3 ) = 235 kJ mol À1 )54 and the strain enthalpy of a typical Si-containing 3-membered ring (157 kJ mol À1 ). (b)DH1 for this reaction used the analogy of the Si-Cl bond enthalpy (501 kJ mol À1 ) in Cl 2 Si(OH) 254 and the p-bond enthalpy obtained by considering the dehydrogenation process of H 2 Si(OH) 2 to give HSi(QO)OH. The enthalpy change for this is given by:DH1 = H D 1 (Si-H) + H D 1(O-H) À H D 1(H-H) À H Dp1 1(Si QO) H Dp1 1(Si QO) = H D 1(Si-H) + H D 1(O-H) À H D 1(H-H) À DH1 H Dp1 1(SiQO)/kJ mol À1 = 408 + 515 À 436 À 156 = 331All the above numbers (except that for H D 1(H-H) 1 ) are from Allendorf and Melius.…”
mentioning
confidence: 99%